(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Administration and control of medium-sized and large computer networks is one o f the most important tasks for any organization. Existing solutions are either too expensive for educational institutions or consists of many separate programs with little or no centralized managements. This work describes system in development based on "Linux” operational system and popular open standards. The central part of the system is LDAP database for information about servers, computers, users etc. This database is used by many less or more independent modules, including mail, proxy and other Internet servers. Access to these services is controlled by firewalls and specialized client/server authorization system, which is needed to prevent password sniffing and other methods of unauthorized access. System is managed from a centralized web-based administration interface. System is under development and will be implemented in several stages, module by module.